2007
DOI: 10.1080/15389580600944250
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Primary and Secondary Impact Loads on the Pelvis during Side Impact

Abstract: Redesigning the center console using less stiff materials and allowing some lateral translation of the seat could aid in reducing pelvic injuries in side impact collisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…1,18 Although side airbags were not found to be protective for pelvic fractures in this study, their primary design is to protect the head and chest regions not the pelvis. 15 Our data may suggest a role for changes in side airbag design. If the increase in BMI may be protective against pelvic fractures, perhaps side airbag design could evolve to replicate the "protective fat" theory of larger BMI occupants.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…1,18 Although side airbags were not found to be protective for pelvic fractures in this study, their primary design is to protect the head and chest regions not the pelvis. 15 Our data may suggest a role for changes in side airbag design. If the increase in BMI may be protective against pelvic fractures, perhaps side airbag design could evolve to replicate the "protective fat" theory of larger BMI occupants.…”
Section: Discussionmentioning
confidence: 85%
“…In contrast, for normal BMI occupants, the center console was more likely to be the source of pelvic injury. Tencer et al 15 has shown the importance of center consoles causing pelvic fracture; however, there was no assessment of the influence of BMI in relation to these injuries. 14,15 Although the biomechanics causing pelvic fractures need further study, occupants who are overweight or obese may not be as likely to be displaced laterally compared with those with a lower BMI.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Furthermore, far-side occupants have almost the same risk for PMI on PMI 1+ and even higher risk for PMI on PMI10+ compared to near-side occupants among lower extremity injuries. The center console has previously been identified as a possible cause for pelvis, hip, and femur fractures for far-side occupants (Banglmaier et al 2003;Tencer et al 2007). It could be a contributing reason for the high risk for PMI among lower extremity injuries among side occupants.…”
Section: Discussionmentioning
confidence: 99%
“…Pelvic fracture incidence in side-impact crashes is 12% (88), and restraint use does not prevent pelvic injuries (2). Lateral impact MVCs generally produce lateral compression patterns of pelvic fractures (6,37).…”
Section: Pelvic Hip and Acetabular Injuriesmentioning
confidence: 99%